Inside job [videorecording (DVD)] - Ferguson, Charles H.; Ferguson, Charles H.; Ferguson, Charles H.; Damon, Matt (Sony Pictures Home Entertainment, 2011)
Provided is an analysis of the global financial crisis of 2008, which at a cost over $20 trillion, caused millions of people to lose their jobs and homes in the worst recession since the Great Depression, and nearly resulted in a global financial collapse. Through exhaustive research, and extensive interviews with key financial insiders, politicians, journalists, and academics, traces the rise of a rogue industry which has corrupted politics, regulation, and academia.